Linking smallholders to markets - Al-Hassan, Ramatu M.; Sarpong, Daniel Bruce; Mensah-Bonsu, Akwasi; Department of Agricultural Economics and Agribusiness, University of Ghana, Legon (International Food Policy Research Institute, 2007)
Access to guaranteed markets for produce and for the acquisition of inputs is a major problem confronting smallholders... The questions addressed by this research are: (a) how can agricultural contracts be enforced in the face of Ghana’s weak legal system; (b) what approaches can be used to certify smallholders for international markets, and (c) what policies are needed to provide infrastructure for export crop development.